THE IMPACT OF CHATGPT-BASED ARTIFICIAL INTELLIGENCE ON THE DEVELOPMENT OF ENTREPRENEURSHIP SKILLS - Sari, Dian Maya; Putri, Wisri Ardhita Manda; Sasmita, Rossy Luckita; Zulfiani, Putri Chairina; Sihombing, Mei Alsih (Jurnal Muara Pendidikan, 2025)
The rapid advancement of artificial intelligence (AI) has brought transformative opportunities for higher education, particularly in strengthening entrepreneurship education. This study examines the impact of ChatGPT-based AI integration on the development of entrepreneurship skills among undergraduate students. Employing a quantitative research design with a sample of 32 students, data were collected through a structured questionnaire assessing four core dimensions of entrepreneurial competence: opportunity recognition, creativity and innovation, business planning, and problem-solving. Descriptive statistics and paired sample t-tests were applied to measure differences between pre-test and post-test scores. The results demonstrate that ChatGPT integration significantly improved students’ entrepreneurship skills, with the greatest gains observed in creativity and innovation, followed by business planning. The overall mean score increased substantially, and all improvements were statistically significant (p < 0.001), indicating a strong positive effect of AI-enhanced learning. These findings highlight ChatGPT’s potential as an effective pedagogical tool for fostering entrepreneurial competencies and preparing students for the challenges of the digital economy. The study recommends further exploration of generative AI applications in entrepreneurship education to optimize skill development and innovation capacity.